Pengembangan Model Teaching Factory Berbasis Industri pada Program Studi Manajemen Tata Hidangan: pada Program Studi Manajemen Tata Hidangan untuk Meningkatkan Kompetensi Profesional Mahasiswa Vokasi - Syafruddin Rais (CV. ITTC INDONESIA, 2026)
Vocational education in the hospitality sector is expected to produce graduates whose competencies meet industry demands. However, a gap still exists between the competencies of students in the Food and Beverage Management Study Program and the requirements of the labor market, particularly in terms of professional skills, industrial work culture, and work readiness. This condition highlights the need for a learning model that effectively integrates educational processes with the needs of the hospitality industry. This study aims to analyze the development of an industry-based Teaching Factory model in the Food and Beverage Management Study Program and its contribution to improving the professional competencies of vocational students. This study employed a qualitative descriptive approach using a case study method. The research was conducted at the Food and Beverage Management Study Program of Batam Tourism Polytechnic. The research informants consisted of the head of the study program, lecturers of practical courses, students, and hospitality industry practitioners selected through purposive sampling. Data were obtained from primary and secondary sources through observation, interviews, documentation, and literature review. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results indicate that the implementation of an industry-based Teaching Factory effectively integrates theoretical learning and practical experience through a learning environment that closely resembles real workplace conditions. The model contributes to the improvement of students’ technical skills (hard skills), soft skills, understanding of industrial work culture, digital competencies, and work readiness. The industry-based Teaching Factory can serve as an effective learning model in hospitality vocational education by strengthening the linkage between higher education institutions and industry while enhancing graduates’ professional competencies and work readiness in accordance with the needs of business and industry.